Elections 1950: The self-election of General Manuel A. Odría - Cobas Corrales, Manuel Efrain (2013)
This article is to build upon the results of a project carried out in 2012, entitled “Process Cancelled Two and a self choice: General Elections of 1936, 1950 and 1962”, the same that had the collaboration of Dr. Simon Escamilo Cardenas . By the nature of the magazine, addresses one of the three elections investigated, considering the 1950, which corresponded to the general election auto Constitutional President Manuel Odría in article discusses the national and international stage before the elections, participants political organizations, the candidates, the media, the electoral universe, and finally results incidents during and after the process and the role played by the armed forces represented by the military junta in the process.